2020
DOI: 10.1093/reep/rez024
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Economic Impacts of Climate Change Using Weather Observations

Abstract: This article reviews methods that use historical data on weather, climate, economic activity, and other variables to statistically measure the effect of climate on economic outcomes. This has been an active area of research for several decades, with many recent developments and discussions in the literature concerning the best way to estimate climate damages. The article first presents a conceptual framework for estimating the costs of climate change impacts. It then examines several approaches proposed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 44 publications
0
73
0
1
Order By: Relevance
“…The risk of extreme weather and climate-related events (e.g., floods and droughts) will probably increase. This would have an impact on several economic sectors (agriculture and tourism, firstly), natural ecosystems and biodiversity, human health, and well-being [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of extreme weather and climate-related events (e.g., floods and droughts) will probably increase. This would have an impact on several economic sectors (agriculture and tourism, firstly), natural ecosystems and biodiversity, human health, and well-being [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…We estimate a reduced form model that does make assumptions on the relationship between weather and outcome variables 21 . Thus, the apple producers might apply agro-managerial practices and our estimated relationship allows for these short-term adaptations 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This method leverages the temporal variation of weather in locations with different baseline climates to estimate the gradients of a response function, thus allowing the marginal effect of weather to vary with climate. Treating weather this way allows models to potentially capture both short-and long-run responses because it exploits cross-sectional variation in climate across space and temporal variation within each spatial unit (Deryugina and Hsiang 2017;Kolstad and Moore 2020). Previous research has shown nonlinear impacts of weather on economic production (Burke et al 2015), agriculture (Schlenker and Roberts 2009) and recreation (Dundas and von Haefen 2020).…”
Section: Weather As An Explanatory Variablementioning
confidence: 99%